Dual stimulation protocol for poor responders, promising approach to increase the success rate of in vitro fertilization cycles - Bahgat, Nagwan A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: It is well known that increasing the number of recruited oocytes affect positively the in vitro fertilization (IVF) cycle outcome. Dual stimulation protocol was invented to increase the number of recruited oocytes in the same cycle through double stimulation and oocyte collection. Methods: This prospective randomized controlled study was done to compare the outcome of one conventional aspiration-embryo transfer cycle with double stimulation- aspiration then frozen transfer cycle. The results were divided into primary outcomes which included the number of oocytes collected, the maturation rate in both times of oocyte collection and in both groups and while the secondary outcome included the oocytes survival rate, fertilization rate, cleavage rate, available blastocyst, and finally pregnancy rate in both arms of the study. Results: A total of 180 patients included. In the first group: 203 oocytes were collected with 151 mature oocytes (maturation rate 74%, fertilization rate of 81.5%), 61 good quality embryos and transferred in 27 cycles (49.6% transfer rate) and 4 got pregnant (14.8% pregnancy rate). In the second group: we got 381 oocytes in total through twice oocyte collection, with 289 mature oocytes (75.8% maturation rate). The second group underwent frozen oocytes transfer cycles. All oocytes were thawed: out of 289 frozen oocytes, 156 survived (53.9% survival rate), we obtained 6 pregnancies (26.1%). Conclusions: Double stimulation protocol followed by double oocytes collection in the same cycle could result in more mature oocytes for patients with poor ovarian reserve who are willing for pregnancy or fertility preservation.